Asian energy factor - "Manning,Robert A." (New York, 2000)
Robert A. Manning debunks key myths about the oil industry: that the world is running out of oil, that the Caspian Basin is the new Gulf, that resource scarcity combined with military modernization, economic buoyancy, and nationalism will lead to military conflict, and that territorial disputes among Asian nations, such as those in the South China Sea, are fuelled by resource competition. His book assesses the energy challenges and strategies of Asian nations and explores the new geopolitics emerging out of their efforts to meet these challenges, the new possibilities for energy to serve as a vehicle for security co-operation, and the implications for American interests and policies in the region.
Keywords: Energy